Effect of Decorin and Aligned Collagen Fibril Topography on TGF-β1 Activation of Corneal Keratocytes - Nathaniel S. Tjahjono; Divya Subramanian; Tarik Z. Shihabeddin; Hudson D. Hicks; Victor D. Varner; W. Matthew Petroll; David W. Schmidtke (Bioengineering)
During corneal wound healing, transforming growth factor-beta 1 (TGF-β1) causes differentiation of quiescent keratocytes into myofibroblasts. Decorin has been investigated as a promising anti-fibrotic therapeutic for corneal healing due to its interaction with TGF-β1, collagen, and cell surface receptors. In this study, a novel microfluidic method for coating aligned collagen fibrils with decorin was developed to mimic the presence of decorin within the corneal stroma. Decorin was found to bind selectively to collagen and remained bound for at least five days. To investigate the effects of decorin coatings on keratocyte activation, primary rabbit keratocytes were cultured in the presence of TGF-β1 for 5 days on substrates with or without decorin and stained for α-smooth muscle actin (α-SMA). The expression of α-SMA was reduced by similar amounts on monomeric collagen (40%), random collagen fibrils (32%), and aligned collagen fibrils (32%) coated with decorin as controls. However, α-SMA expression was differentially expressed between the collagen substrates not coated with decorin, with significantly lower expression on uncoated aligned collagen fibrils compared to uncoated collagen monomers. Addition of decorin directly to culture media, had a limited effect on reducing myofibroblast differentiation. Taken together, these results demonstrate the importance of topography and ECM composition on keratocyte activation.